BLOCKCHAIN TECHNOLOGY –REVAMPING THE INDIAN FINANCIAL SECTOR LANDSCAPE AND ROADBLOCKS AHEAD - Dr. Namrata Prakash , Shivani Solanki , Emmanuel Elgin Gabriel , Dr. Monika Bangari (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Blockchain is evolving as a disruptive core technological force. This force is capable of transforming the financial services industry and also modified business models. It is providing for a faster, inexpensive, more safe and transparent day-to-day functioning of businesses. Blockchain is called a distributed ledger technology that was initially created to facilitate Bitcoin transactions. Block chain was developed in 2009 to help individuals and organizations to direct transactions without the need for any intermediary institution or a central bank. It uses complex algorithms to confirm transactions. Blockchain has been helping users to carry out trade and commerce across the globe without the need for payment processors, custodians, and settlement and reconciliation entities. Blockchain technology has the potential to revolutionize the way governments, the financial sector and companies are functioning and can ignite the fourth Industrial Revolution across the world. This paper is an attempt to check out significant blockchain implementations in India done so far for embracing the technology, both within and outside the financial domain and problems in the implementation of blockchain technology in India.